Clinical improvements following bilateral anterior capsulotomy in treatment-resistant depression. Issue 6 (15th December 2016) - Subramanian, L.; Bracht, T.; Jenkins, P.; Choppin, S.; Linden, D. E. J.; Phillips, G.; Simpson, B. A.
Abstract : Background: The purpose of this study was to evaluate a programme of lesion surgery carried out on patients with treatment-resistant depression (TRD). Method: This was a retrospective study looking at clinical and psychometric data from 45 patients with TRD who had undergone bilateral stereotactic anterior capsulotomy surgery over a period of 15 years, with the approval of the Mental Health Act Commission (37 with unipolar depression and eight with bipolar disorder). The Beck Depression Inventory (BDI) before and after surgery was used as the primary outcome measure. The Montgomery–Asberg Depression Rating Scale was administered and cognitive aspects of executive and memory functions were also examined. We carried out a paired-samples t test on the outcome measures to determine any statistically significant change in the group as a consequence of surgery. Results: Patients improved on the clinical measure of depression after surgery by −21.20 points on the BDI with a 52% change. There were no significant cognitive changes post-surgery. Six patients were followed up in 2013 by phone interview and reported a generally positive experience. No major surgical complications occurred. Conclusions: With the limitations of an uncontrolled, observational study, our data suggest that capsulotomy can be an effective treatment for otherwise TRD. Performance on neuropsychological tests did not deteriorate.